PENERAPAN METODE RAD UNTUK PENGEMBANGAN SISTEM INVENTORI OBAT BERBASIS WEB MENGGUNAKAN FRAMEWORK LARAVEL (STUDI KASUS PADA KLINIK SUKARAYA MEDIKA KABUPATEN BEKASI) - Ahmad Turmudi Zy (Jurnal Pelita Teknologi, 2022)
Abstract Over time, the use of information and technology systems in bussines development has become one of the main factors to improve the quality of company performance in carrying out daily businesses processes, especially for a business that have a large and varied inventory of merchandise such as the health and medicine business sector. Sukaraya Medika Clinic is a health facility located in Krang Bahagia District Bekasi. This clinic, which has been operating for a long time, has served the community both medical and medicine services. In managing drug inventory data, the clinic is still in the simple category, namely by recording in a book without an integrated information system. It can be not easy if you want to check drug stocks in realtime because of the many types of drugs available. Based on these problems, the authors aims to create a web-based inventory system using laravel framework that can solve the problems faced by Sukaraya Medika Clinic. The final result of this research is to create a web-based inventory system that can be a solution to the problems of the Sukaraya Medika Clinic. terhadap masalah Klinik Sukaraya Medika.